Burnout Syndrome in University Teachers during Virtual Classes - López De La Cruz, Edgardo Cristiam Iván (2020)
Objective. To determine the level of burnout syndrome presented by university teachers during virtual classes. Methods. A simple descriptive design was used, the burnout syndrome was determined based on three dimensions: emotional fatigue, depersonalization and personal fulfillment. The population was made up of all the teachers of Universidad de Huánuco, 531 teachers during the 2020-II period. The instrument for collecting these data was based on the transparency section of the official website of Universidad de Huánuco. The sample was determined probabilistically by strata, resulting in a total of 223 teachers. Statistics used were descriptive, where summary measures were considered. Results. Regarding the emotional fatigue dimension, it was obtained that 46.3% of teachers presented low emotional fatigue and only 35.2% of teachers obtained a high level of emotional fatigue, in relation to the delivery of virtual classes. Regarding depersonalization dimension. Mixed results were obtained, since 40.1% of the teachers obtained a high level of depersonalization, while 44.1% had a low level, and the remaining a medium level. In personal fulfillment dimension, 59% of the teachers obtained a low level. Conclusion. Teachers presented the burnout syndrome at a low level, specifically in the dimension of emotional exhaustion in the context of virtual classes, reflected in 46.3% of the cases.